CYTOTOXIC EFFECTS OF ALBIZIA ZYGIA (DC) J. F. MACBR, A GHANAIAN MEDICINAL PLANT, AGAINST HUMAN T-LYMPHOBLAST-LIKE LEUKEMIA, PROSTATE AND BREAST CANCER CELL LINES - Appiah-opong, Regina; Asante, Isaac Kwadwo; Safo, Dorcas Osei; Tuffour, Isaac; Ofori-attah, Ebenezer; Uto, Takuhiro; Nyarko, Alexander Kwadwo (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objectives of this study were to investigate the cytotoxic effects of extracts and fractions of Albizia zygia roots (AZR) on human T-lymphoblast-like leukemia (Jurkat), prostate cancer (LNCap) and breast cancer (MCF-7) cells and the apoptotic effect in Jurkat cells. Methods: Aqueous and hydroethanolic extracts were prepared and tested for cytotoxic effects on the cell lines using the tetrazolium-based colorimetric assay. Apoptosis induction was determined by DNA fragmentation, cell morphological changes, flow cytometric and mitochondrial membrane potential assays. Results: Both aqueous and hydroethanolic extracts were more cytotoxic to Jurkat cells than the other cell lines, with selective index (SI) values of 104.4 and 86.6, respectively. The SI values of the extracts on LNCap cells were 9.0 and 35.4, respectively. Some of the fractions were non-cytotoxic. Nevertheless petroleum ether fraction was cytotoxic towards MCF-7 cells with SI value of 2.4. The hydroethanolic extract exhibited apoptosis via induction of DNA fragmentation in Jurkat cells. Cell morphological changes were consistent with the extract-mediated cytotoxicity and DNA fragmentation. Flow cytometric and mitochondrial membrane potential assays also showed significant apoptotic induction confirming apoptosis by the AZR extract. Conclusion: This study has shown that AZR possesses anticancer activity by demonstrating a high selective toxicity against Jurkat cells. Furthermore, the hydroethanolic extract induced apoptosis in the Jurkat cells. Albizia zygia roots may be a source of novel compounds for the development of new anti-cancer agents. Keywords: Albizia zygia, Cancer cells, Cytotoxicity, Apoptosis